KINERJA DINAS SOSIAL PROVINSI RIAU (STUDI KASUS: PEMULANGAN ORANG TERLANTAR DI KOTA PEKANBARU) - Ilham Hidayat Alne; Harapan Tua Ricky Freddy Simanjuntak (Journal Publicuho, 2022)
This writing aims to find out the performance of the Riau Provincial Social Service in handling the problem of repatriation of displaced people in the city of Pekanbaru to create social welfare for displaced people. Abandonedness is experienced due to the mobility of residents from one area to another with the aim of achieving a better life. Pekanbaru is one of the destinations because it is the capital of riau province that has promising jobs. Riau Provincial Social Service accommodates the repatriation of displaced people to their hometowns. This research aims to find out how the performance of riau provincial social services (case study: repatriation of displaced people in pekanbaru city). The research method used is a qualitative research method with a case study approach that is descriptive analysis. Research is conducted by collecting various information, processed and analyzed based on existing data based on how the organizational performance piercing used in this study. The result of this study is the creation of social care and welfare for displaced people.